Advances in Radiation Oncology in Lung Cancer - Jeremic, Branislav; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Although decades of laboratory and clinical research have led to incremental improvement in treatment outcome, lung cancer remains one of the most deadly diseases. In the second, completely updated edition of this comprehensive book, many of the world$1 (Bs leading lung cancer specialists discuss the recent advances in the radiation oncology of lung cancer and reflect on the latest research findings. The first three sections cover the basic science of lung cancer, clinical investigations, including histology and staging, and a wide range of fundamental treatment considerations. Current treatment strategies for nonsmall cell and small cell lung cancer are then explained and evaluated in detail, with due attention to novel approaches that promise further improvements in outcome. The various types of treatment-related toxicity are discussed, and quality of life studies and prognostic factors are also considered. After evaluating the latest technological and biological advances, including IMRT, IMAT, cyber knife treatment, and tomotherapy, the book concludes by thorough consideration of specific aspects of clinical research in lung cancer.s
Basic science of lung cancer -- clinical investigations -- basic treatment considerations -- current treatment strategies in early-stage non-small cell lung cancer -- current treatment strategies in locally advanced non-small cell lung cancer -- current treatment strategies in small cell lung cancer -- treatment in specific patient groups and other settings -- treatment-related toxicity -- quality of life studies and prognostic factors -- technological advances in lung cancer -- biological advances in lung cancer -- clinical research in lung cancer.
Keywords: Medicine; Radiology, Medical; Radiotherapy; Pneumology; Oncology; Thoracic surgery; Medicine & Public Health; Imaging / Radiology; Radiotherapy; Oncology; Thoracic Surgery; Pneumology/Respiratory System